Bribing to escape poverty in Africa - Simplice Asongu; Samba Diop (African Governance and Development Institute (AGDI), 2022)
This study assesses the nexus between bribery and poverty, contingent on the macroeconomic environment within the remit of inflation in Africa. The Afrobarometer survey is used. Our data cover 38 countries consisting of three rounds of survey and a sample of 151,345 individuals. The empirical strategy is based on multi-level mixed-effects ordered logit regression. The results reveal that while poverty has a positive effect on the spread of bribery, inflation can mitigate the impact. The impact is stronger for people living without basic necessities such as food, water and medical care. In other words, the attendant results indicate that the impact of poverty on bribery becomes negative when inflation increases. The findings are robust to inter alia: (i) multi-level mixed effects ordered logistic models for fragile and conflict-affected countries with the food price index at a market level as the mitigating variable and (ii) estimations with the continuous indicator of bribery and experienced poverty at the country level. Policy implications are discussed.
Keywords: D31; I10; I32; K40; O55; 330; Inclusive development; Poverty; Bribery; Africa